Autecology of Nepenthes spp. in Peat Swamp and Heath Forest Pematang Gadung, West Kalimantan - Nofi Utari; Sulistijorini Sulistijorini; Nunik Sri Ariyanti (Universitas Gadjah Mada, 2023)
Nepenthes occur in various habitat types in West Kalimantan. But some species are categorized as vulnerable on the IUCN red list. Autecological studies of Nepenthes spp. are required for species management and conservation. The study aimed to analyze species diversity, distribution pattern, association, and environmental factors that correlated with Nepenthes spp. at peat swamp and heath forest in Pematang Gadung. Data was collected in September 2021 by purposive sampling on 60 plots measuring 3 x 3 m2 in each habitat type. Species diversity was analyzed based on the presence and abundance of species in the plots. The distribution pattern was determined using a standardized Morisita index (Ip). Meanwhile, the association type was determined based on the Jaccard index (JI). Environmental data were analyzed by Canonical Correspondence Analysis (CCA) using Past Version 4.03. This study found six wild species in a peat swamp and four species in a heath forest. The population of Nepenthes spp. has clumped distribution pattern with Ip>0. Nepenthes spp. are associated with plants such as Barringtonia racemosa, Syzygium sp., Nephrolepis biserrata, and Campnosperma auriculatum. The result of CCA revealed that environmental factors in both habitat types affected the presence of each Nepenthes species. The air temperature, humidity, soil moisture, and light intensity show different influences on different species.